Report on Afghanistan - Nayar, Kuldip, 1923- (New Delhi Allied Publishers Private Limited, 1981)
Report fashioned out of visits and interviews by an Indian journalist
Include Appendix, Bibliography, Reference and Index
Keywords: Afghanistan -- Politics and government